Призвание: очерки / Г. А. Губанов - Губанов Геннадий Андреевич (Издательство ДОСААФ, 1982)
Экземпляры: КХ (20160119) / Инвентарный номер: 769042 / Цена: 0.55 / Сис.шифр: 358.5 / Авт.знак: Г 93 / ГРНТИ: 78.01 / ББК: 68